2023
DOI: 10.2147/jpr.s398578
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CT-Guided Pulsed Radiofrequency Combined with Ozone Injection on Zoster-Associated Pain: A Retrospective Study

Abstract: Purpose Globally, the incidence of herpes zoster (HZ) is increasing, and the resulting zoster-associated pain (ZAP) severely affects the quality of life of patients. Therefore, active treatment of ZAP and prevention of postherpetic neuralgia (PHN) are very important for patients in the early stage of the disease. This retrospective observational study aimed to evaluate the effect of CT-guided pulsed radiofrequency (PRF) combined with ozone injection on zoster-associated pain. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[ 53 ] Specifically, it has been increasingly utilized for the relief of PHN in recent years, demonstrating both safety and efficacy. [ 54 ] For “prevention,” the prevention of PHN has been a prominent area of research in recent years, with a focus on interventions such as vaccination, [ 55 ] gabapentinoids, [ 56 ] epidural block. [ 57 ] For “herpes zoster,” the occurrence of PHN is causally associated with HZ.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53 ] Specifically, it has been increasingly utilized for the relief of PHN in recent years, demonstrating both safety and efficacy. [ 54 ] For “prevention,” the prevention of PHN has been a prominent area of research in recent years, with a focus on interventions such as vaccination, [ 55 ] gabapentinoids, [ 56 ] epidural block. [ 57 ] For “herpes zoster,” the occurrence of PHN is causally associated with HZ.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that ozone therapy has almost no side effects and is safe for clinical application 15 . Presently, it has been reported that ozone therapy can relieve HZ-associated neuralgia 16,17 . However, previous studies were retrospective and conducted on a small sample size.…”
mentioning
confidence: 99%
“… 15 Presently, it has been reported that ozone therapy can relieve HZ-associated neuralgia. 16 , 17 However, previous studies were retrospective and conducted on a small sample size. Therefore, in the present study, we focused on the clinical efficacy of dorsal root ganglion (DRG) ozone injection combined with pulsed radiofrequency for treating acute HZ neuralgia in middle-aged and elderly adults, as well as explored its preventive effect on the occurrence of PHN.…”
mentioning
confidence: 99%